Stimuli‐responsive nanotherapeutics for precision drug delivery and cancer therapy. (4th May 2018) - Qiao, Yiting; Wan, Jianqin; Zhou, Liqian; Ma, Wen; Yang, Yuanyuan; Luo, Weixuan; Yu, Zhiqiang; Wang, Hangxiang
Abstract : Cancer remains one of the world's leading causes of death. However, most conventional chemotherapeutic drugs only show a narrow therapeutic window in patients because of their inability to discriminate cancer cells from healthy cells. Nanoparticle‐based therapeutics (termed nanotherapeutics) have emerged as potential solutions to mitigate many obstacles posed by these free drugs. Deep insights into knowledge of the tumor microenvironment and materials science make it possible to construct nanotherapeutics that are able to release cargoes in response to a variety of internal stimuli and external triggers. Therefore, such highly sophisticated nanosystems could help impede the premature release of toxic drugs in the blood circulation or healthy tissues, thus enhancing the safety profiles of encapsulated drugs. In this context, this review offers a comprehensive overview of several specific stimuli, including internal stimuli (e.g., pH, temperature, enzyme, redox, and H2 O2 ) and external stimuli (e.g., magnetic, photo, and ultrasound). We envision that applications of these smart nanotherapeutics can benefit cancer patients and provide a good chance for clinical translation of many nanoparticle formulas. This article is categorized under: Therapeutic Approaches and Drug Discovery > Nanomedicine for Oncologic Disease Diagnostic Tools > Diagnostic Nanodevices Diagnostic Tools > in vitro Nanoparticle‐Based Sensing Abstract : Nanotherapeutics have emerged as potential solutions to fulfill the promise of Paul Ehrlich's magic bullet concept. This review offers a comprehensive overview of the construction of nanotherapeutics that are able to precisely release drug cargoes in response to a variety of internal stimuli and external triggers. The applications of these smart systems can benefit cancer patients and provide a good chance for clinical translation of many nanoparticle formulas.